MdATG18a overexpression improves tolerance to nitrogen deficiency and regulates anthocyanin accumulation through increased autophagy in transgenic apple. (28th December 2017) - Sun, Xun; Jia, Xin; Huo, Liuqing; Che, Runmin; Gong, Xiaoqing; Wang, Ping; Ma, Fengwang
Abstract: Nitrogen (N) availability is an essential factor for plant growth. Recycling and remobilization of N have strong impacts on crop yield and quality under N deficiency. Autophagy is a critical nutrient‐recycling process that facilitates remobilization under starvation. We previously showed that an important AuTophaGy (ATG) protein from apple, MdATG18a, has a positive role in drought tolerance. In this study, we explored its biological role in response to low‐N. Overexpression of MdATG18a in both Arabidopsis and apple improved tolerance to N‐depletion and caused a greater accumulation of anthocyanin. The increased anthocyanin concentration in transgenic apple was possibly due to up‐regulating flavonoid biosynthetic and regulatory genes ( MdCHI, MdCHS, MdANS, MdPAL, MdUFGT, and MdMYB1 ) and higher soluble sugars concentration. MdATG18a overexpression enhanced starch degradation with up‐regulating amylase gene ( MdAM1 ) and up‐regulated sugar metabolism related genes ( MdSS1, MdHXKs, MdFK1, and MdNINVs ). Furthermore, MdATG18a functioned in nitrate uptake and assimilation by up‐regulating nitrate reductase MdNIA2 and 3 high‐affinity nitrate transporters MdNRT2.1/2.4/2.5. MdATG18a overexpression also elevated other important MdATG genes expression and autophagosomes formation under N‐depletion, which play key contributions to above changes. Together, these results demonstrate that overexpression of MdATG18a enhances tolerance to N‐deficiencies and plays positive roles in anthocyanin biosynthesis through greater autophagic activity. Abstract : Autophagy plays a critical role in recycling and remobilization of nitrogen. Here, overexpression of MdATG18a enhanced tolerance to N‐depletion in both Arabidopsis and apple. Overexpression of MdATG18a in apple accumulated more anthocyanin and improved nitrate uptake by up‐regulating anthocyanin‐related genes and some nitrate transporters, respectively. These results were possibly because of increased autophagy activity in transgenic lines under N deficiency.